Freud, forgotten Neurologist - JMS Pearce (Advances in Clinical Neuroscience & Rehabilitation, 2019)
For a five-year period, before Sigmund Freud embarked on his original studies of psychological mechanisms, nomenclature, and psychoanalysis, he had extensive neuropathological training under von Brücke and executed research into neuronal cytoarchitecture and neural tracts. Influenced by Charcot and Theodor Meynert he carried out and published important clinical studies on aphasia and cerebral diplegia. He strived to carry his scientific discipline into his psychoanalytical work. As a Neurologist his role is underestimated.